Penerapan Manajemen Risiko Pembiayaan Bermasalah pada Produk Business Banking - Hendy Herijanto; Mia Mahdania Ulfani; Shofiah Tidjani (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2022)
As the economic sector of Indonesia has developed, Islamic banking has emerged as a solution to the resulting issues. As is widely known, Islamic Sharia has already developed Islamic economies in other countries. Moreover, Islamic banks provide a wide range of products and services to the public, such as the Bank Syariah Indonesia (BSI) Bintaro Branch Office, which provides financing options to individuals seeking to expand their enterprises. Including business financing, all forms of transactional activities in Islamic banks will always involve risks. This study aims to investigate the risks connected with the financing products supplied by the Bank Syariah Indonesia and to determine how to lessen the risks associated with business financing products and what steps may be taken to overcome the financing default. This study applies qualitative research using a case study research approach to describe and explain pertinent facts and data collected through interviews and other data collectiong from the institution. This study's findings indicate that risk management was performed at BSI Bintaro in line with specified rules, including the application of the 5C principles in examining the provision of financial viability to prospective consumers. However, BSI  Bintaro must address issues such as internal hazards and the elimination of tolerance analysis. Customers and banks should maintain a high level of professionalism to develop mutually advantageous business partnerships.